Analisis Kinematika pada Quick Return Mechanism dengan Menggunakan Metode Bilangan Kompleks - Nazaruddin Nazaruddin; Warman Fatra (Proksima, 2023)
Kinematics analysis includes analysis of position, velocity and acceleration of the rods of a mechanism. The complex number method is a kinematic analytical way to express position, velocity and acceleration vectors in the form of complex numbers. The first step that needs to be done is to determine the position vector of the point to be analyzed, then determine the velocity and acceleration vectors by differentiating with time. After that is done, then the algorithm can be made. The mechanism used for this study is the quick return mechanism. The assumed data for this analysis is the angular velocity of rod 2 is 19.0986 rpm and the acceleration of rod 2 is 0 rad/s2. The results of the position analysis show that if rod 2 rotates one full rotation (360o), then rod 4 rotates about 1/6 circle (232.72o - 294.12o) and the slider moves along the X axis (406.939 - 504.111). The maximum speed behind the slider is 121.45 mm/s while the maximum speed forward for the slider is 101.09 mm/s. A large change in velocity (acceleration) is needed when bar 4 and the slider change direction (from CW to CCW or vice versa), this is indicated by a decrease and increase at the beginning and end of the graphic with significant acceleration